Hydrogen peroxide production via a redox reaction of N, N′-dimethyl-2, 6-diaza-9, 10-anthraquinonediium by addition of bisulfite. Issue 79 (19th September 2018) - Kolesnichenko, Igor V.; Escamilla, P. Rogelio; Michael, Jason A.; Lynch, Vincent M.; Vanden Bout, David A.; Anslyn, Eric V.
Abstract : We demonstrate that bisulfite can be used for reduction of a highly electrophilic anthraquinone derivative, N, N ′-dimethyl-2, 6-diaza-9, 10-anthraquinonediium (DAAQ), and subsequent autoxidation generates an equivalent of hydrogen peroxide. Abstract : We demonstrate that bisulfite can be used for reduction of a highly electrophilic anthraquinone derivative, N, N ′-dimethyl-2, 6-diaza-9, 10-anthraquinonediium (DAAQ), and subsequent autoxidation generates an equivalent of hydrogen peroxide. The mechanism for DAAQ reduction by bisulfite, DAAQ electrochemistry, and use of a simple test strip assay for H2 O2, are described.